2016
DOI: 10.3892/ol.2016.5056
|View full text |Cite
|
Sign up to set email alerts
|

mTOR downstream effectors, 4EBP1 and eIF4E, are overexpressed and associated with HPV status in precancerous lesions and carcinomas of the uterine cervix

Abstract: The present study aims to investigate the expression levels of two critical mammalian target of rapamycin (mTOR) downstream effectors, 4E binding protein 1 (4EBP1) and eukaryotic initiation factor 4E (eIF4E) proteins, in precancerous squamous intraepithelial lesions and cancer of the uterine cervix, and their association with human papilloma virus (HPV) infection status. Uterine cervical biopsies from 73 patients were obtained, including 40 fresh-frozen samples and 42 archival formalin-fixed, paraffin-embedded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…Housekeeping mRNAs, for example, cytoskeleton proteins, require a low level of eIF4E, whereas proto-oncogenic and prosurvival proteins such as c-Myc, cyclin D1, Pim-1, survivin, Bcl-2, VEGF have a much higher dependency on eIF4E for translation [11,12]. These mRNAs are termed as 'weak mRNAs' and are greatly influenced by an increase in eIF4E levels, observed in 30% of human cancers [13][14][15]. The availability of eIF4E is regulated by 4E-binding proteins, which compete with eIF4G for a common surface to bind to eIF4E [4,16,17].…”
Section: Dual Targeting Of Mnks Reviewmentioning
confidence: 99%
“…Housekeeping mRNAs, for example, cytoskeleton proteins, require a low level of eIF4E, whereas proto-oncogenic and prosurvival proteins such as c-Myc, cyclin D1, Pim-1, survivin, Bcl-2, VEGF have a much higher dependency on eIF4E for translation [11,12]. These mRNAs are termed as 'weak mRNAs' and are greatly influenced by an increase in eIF4E levels, observed in 30% of human cancers [13][14][15]. The availability of eIF4E is regulated by 4E-binding proteins, which compete with eIF4G for a common surface to bind to eIF4E [4,16,17].…”
Section: Dual Targeting Of Mnks Reviewmentioning
confidence: 99%
“…Previous studies have suggested that the aberrant activation of the eIF4F complex is implicated in the initiation and promotion of cervical carcinogenesis-mediated by HPV. Although the relationship between HPV infection and activation of the eIF4F complex is not completely understood, histopathological evidence indicates the involvement of eIF4E alteration in the progression of cervical cancer [13,14]. In this study, we investigated the mechanisms through which E6 proteins of low-risk (6E6) and high-risk (16E6, 18E6, and 52E6) genotypes can modify the activity of the eIF4E protein and their possible effects on the downstream targets of the eIF4F complex, CCND1, and ODC1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the increased levels of eIF4E during cervical carcinogenesis cause an increase in the rate of synthesis of the early oncoproteins of high-risk HPV (HR-HPV) [14,25]. This finding is related to the indirect effect of E6 oncoproteins on the transcriptional activation of the eIF4E promoter via the stimulation of p53 degradation.…”
Section: High-risk Human Papillomavirus E6 Proteins Increase Phosphormentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, signaling activation of the protein kinase mTOR, which is involved in protein synthesis, has been noted in both HPV-negative and HPV-positive cervical cancer tissues and cell lines; mTOR inhibitors have also shown to effectively decrease the activity of mTOR along with remarkably decreasing tumor burden. [ 4 ] Li et al . [ 30 ] also identified increased levels of the oncoprotein HBXIP in patients with squamous cell carcinoma of the cervix compared to normal cervical epithelial and that high expression of this protein was related to invasive and metastatic disease with overall lower survival rates.…”
Section: Discussionmentioning
confidence: 99%